In vitro vizsgálati modellek eredményeinek összehasonlítása a kúpok hatóanyagleadása szempontjából [Comparison of in vitro model examinations with respect to drug release from suppositories] - Regdon Géza (ifj.) (ACTA PHARMACEUTICA HUNGARICA, 2000)
9 lipophilic suppository bases with different physical-chemical parameters were examined. Buspiron-hydrochloride, an anxiolytic drug with good water-solubility was used - partly as a model - as a pharmacon, in a concentration of 10.0 mg/2.00g. The rate and extent of in vitro drug release was monitored with static and dynamic methods. Kidney-dialysing membranes with various surfaces were used. The quantitative measurements were carried out spectrophotometrically and the amount of the diffused drug was determined at λ= 298 nm. The mean values were calculated from 5 parallel measurements each time. The percentage values of in vitro relative availability revealed that the results of the two static diffusion studies did not differ significantly (p <0.05) and were almost independent of the size of the membrane surface. The results of the dynamic diffusion method were well-reproducible but were vehicle-dependent. The process of release was characterized by the mathematical transformation of the release curves, while the correlation coefficients described the closeness of the relation. Two German vehicles, namely Witepsol H 15 with a medium hydroxyl value and Massa Estarinum 299, and a French vehicle, Suppocire AS2X were found to be excellent for the formulation of suppositories containing Buspiron-hydrochloride.